2023
DOI: 10.3390/pathogens12101240
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Toxoplasma gondii Seroprevalence in Pregnant Women: A Cross-Sectional Study in Belgrade, Serbia

Ljiljana Marković-Denić,
Milena Stopić,
Branko Bobić
et al.

Abstract: Toxoplasmosis, caused by the cosmopolitan protozoan Toxoplasma gondii, has particular implications during pregnancy due to the possible transmission of infection to the fetus. Very few studies have assessed seroprevalence and the risk factors for toxoplasmosis in healthy pregnant women. The aim of this study was to examine the seroprevalence of T. gondii infection in healthy pregnant women and to identify the associated risk factors for toxoplasmosis. The cross-sectional study involved 300 healthy pregnant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Our study found significantly higher toxoplasma seropositivity among residents of suburban and rural areas (27.4%) compared to urban areas (17.1%). Significantly higher seroprevalence in rural areas was also observed in a Romanian study (46 vs. 36%) [ 31 ], while it was of borderline significance in a Serbian study (22.5 vs. 11.5%) [ 22 ]. In Slovakia, women who lived in Bratislava’s surroundings had a considerably higher seropositivity rate (63.5%) than those who lived in Bratislava (36.6%) [ 39 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our study found significantly higher toxoplasma seropositivity among residents of suburban and rural areas (27.4%) compared to urban areas (17.1%). Significantly higher seroprevalence in rural areas was also observed in a Romanian study (46 vs. 36%) [ 31 ], while it was of borderline significance in a Serbian study (22.5 vs. 11.5%) [ 22 ]. In Slovakia, women who lived in Bratislava’s surroundings had a considerably higher seropositivity rate (63.5%) than those who lived in Bratislava (36.6%) [ 39 ].…”
Section: Discussionmentioning
confidence: 93%
“…Comparing the overall T. gondii seropositivity, the detected seroprevalence rate in Croatia (20.2%) was similar to the seroprevalence in Italy (20.9%, Palermo, 2012–2022) [ 18 ], Spain (21%, Albacete, 2006) [ 19 ], Poland (22.3%, 2018–2019) [ 20 ] and northern Kosovo and Metohija (24.1%, 2011–2012) [ 21 ]. Lower seropositivity was found in Serbia (12.7%, Belgrade, 2018–2019) [ 22 ], the United Kingdom (9.1%, Kent, 1999–2001; 17.32%, London, 2006–2008) [ 23 , 24 ] and in Turkey (14%, Karabük, 2008) [ 25 ], while higher seropositivity was found in France (31.3%, 2016) [ 26 ], Germany (39.5%, 2006–2018) [ 20 ], and the Netherlands (40.5%, 1995–1996) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…We selected the minimum sufficient adjusted set of confounders using the modified disjunctive cause criterion, informed by evidence in the current literature and a directed acyclic graph (DAG) (Fig 2) (1,7,(13)(14)(15)(16)(17). As cat ownership is not an important risk factor for T. gondii infection, and pet ownership information was not collected in the 2012-2014 NHANES, cat ownership was not included as a covariate (18)(19)(20)(21)(22)(23). Because the NHANES categorizes subjects over the age of 80 years as "80+", we grouped the age variable into decades as follows: "6-9";…”
Section: Methodsmentioning
confidence: 99%